HEALTH EDUCATION USING MATCHING IMAGES TO ENHANCE PRESCHOOLERS’ KNOWLEDGE ON FRUITs AND VEGETABLES - Alfonsa Reni Oktavia ,; Ricca Olivia Nastasya ,; Dwi Ayu Lestari ,; Dewi Susanti ,; Bias Talenta , (International Journal of Social Science, 2024)
WHO suggests that people of all ages should consider increasing their intake of fruit and vegetables. It has a positive impact on learning potential and wellbeing in children and adolescents.The consumption of vegetables and fruit by children is influenced by parental knowledge and motivation. The use of educational nutrition games with puzzle-based learning aims to enhance children''s understanding and reduce the sense of obligation. Tthe consumption of vegetables and fruit by children is relatively low in early childhood education in Kebayoran Lama the research project entitled " The Effect Of Health Education Through The Use Of Media Games Matching Images Derived Via This research used a quasi-experimental approach with a one-group pretest-posttest design.Moreover, this research employed a comprehensive sampling technique, which resulted in 25 respondents. The place of this study was kindergarten, Jakarta. The data was collected using a pre-test and post-test questionnaire for media games involving image matching. This study used a paired t-test to determine the impact of health education using media games on knowledge about fruit and vegetables. The results of the pretest and posttest were then analyzed, so the gap between before and after the introduction of fruit and vegetables could be seen. the average knowledge of preschoolers on their score before being given health education about vegetables and fruit shows the mean value of 55.3 with a standard deviation of 21.0, and the average knowledge of preschoolers based on their knowledge score after being given health education about vegetables and fruit shows the mean value of 81.3 with a standard deviation of 15.5. The result of paired T Test shows a p value of 0.000 (p <0.05). There is a significant increase in knowledge level regarding fruit and vegetable in preschool children with image matching game media. There is a change in children''s habit of consuming fruits and vegetables after the image matching game. Image matching games are effective as educational media in increasing children''s knowledge and interest in consuming fruit and vegetables